Griseofulvin vs terbinafine for paediatric tinea capitis: When and for how long. Issue 10 (18th August 2019) - Bar, Jonathan; Samuelov, Liat; Sprecher, Eli; Mashiah, Jacob
Summary: Outbreaks of tinea capitis (TC) can be a source of medical and economic burden for healthcare systems; Griseofulvin and terbinafine are considered to be effective first‐line treatments for TC. In order to compare the efficacy of griseofulvin and terbinafine for the treatment of TC in a paediatric population of African immigrants in the Tel Aviv area, we conducted a retrospective cohort study of all cases of TC diagnosed and treated between March 2016 and February 2018 at a dedicated TC paediatric dermatology clinic at the Tel Aviv Medical Center (which serves as a referral centre for the paediatric refugee population in the Tel Aviv metropolitan area). Epidemiologic, clinical and laboratory data were collected, and 304 patients were included. Trichophyton violaceum (TV), Trichophyton soudanense (TS) and Microsporum audouinii (MA) were the prominent causative organisms. Treatment with griseofulvin suspension for 12 weeks was compared with (a) griseofulvin suspension for 8 weeks and with (b) terbinafine tablets for 4 weeks. There was no statistically significant difference between the groups regarding age, sex, country of birth, ethnicity and the causative organism. Twelve weeks of griseofulvin treatment had a statistically significant better cure rate than 4 weeks of terbinafine. Treatment was significantly more effective when TC was due to infections with MA and TS as compared with TV. No statistically significant difference was observed between 12‐ and 8‐week treatment with griseofulvin.